Alat Pengurai Sabut Kelapa dengan Blade Portable Untuk Menghasilkan Cocofiber dan Cocopeat - Sepriyanto Sepriyanto (Jurnal Civronlit Unbari, 2018)
Coconut as one of the leading plantation products in Jambi province, currently only rely on copra and coconut shell charcoal as the resulting product. Coconut removal as a by-product of coconut has not been utilized optimally. Coconut husk which is processed with precise and appropriate can produce high value product. This research aims to design, make and test the tool to decompose the coconut scale of household scale. Coconut coir decomposers are made with 1000x700x 1080mm tool dimensions, the driver uses 6.5 HP gasoline engine and an average engine capacity of 10 kg / hour. Knife cut (blade) on this tool can be removed (portable) so it can be tailored to the needs. The test was conducted to determine the effect of blade amount and time to the percentage of cocofiber and cocopeat produced. Number of blades varied ie 5 blades and 10 blades. Decomposition time varied from 1 minute, 2 minutes, 3 minutes, 4 minutes and 5 minutes, with a 650 rpm engine speed. The results of this study recommend to use 10 blades with a decomposition time for 5 minutes. The results obtained from the recommendation are cocofiber that decomposes as much as 32%, which does not decompose as much as 10% and cocopeat produced as much as 58%.Keywords:  blade, portable, cocofiber, cocopeat.